Release and removal of intracellular and extracellular microcystins (RR, LR) using nano-Fe3O4 particles as a coagulant aid for polyaluminum chloride - Hanshu Zhang; Ming Cheng; Bo Zhang (Water-Energy Nexus)
The outbreak of algal blooms caused by cyanobacteria has led to a significant concern regarding water safety due to the release of microcystins. This study aimed to investigate the release and removal of microcystins (RR, LR) using coagulant polyaluminum chloride (PAC) with the assistance of nano-Fe3O4 particles. The findings indicate that the addition of PAC alone resulted in the rupture of Microcystis aeruginosa cells, leading to the release of microcystins into the water. PAC alone faced challenges in coagulating and removing the extracellular microcystins, especially at low dosages, but increasing the dosage of PAC could promote the release of intracellular microcystins. When combined with nano-Fe3O4, even a low concentration of PAC exhibited effective removal of microcystins in water. The presence of nano-Fe3O4 facilitated the hydrolysis of PAC, resulting in the production of Alc, which enhanced the coagulation performance of PAC. Furthermore, the addition of nano-Fe3O4 significantly improved the removal rate of microcystins by coagulant PAC under different pH conditions. Notably, at pH 5, the residual amount of microcystins was only about 7% compared to PAC alone. This study holds great significance in terms of achieving safer and more economical removal of microcystins from water.